Analysis of idiomatic expressions in adele’s song lyrics - Trần, Hoài Hưng (2016)
The study entitled “Analysis of idiomatic expressions in the Adele’s song lyrics” focused on two aspects: (1) to find the classifications of idiomatic expressions and (2) to analyze the meanings of idiomatic expressions found in the song lyrics of Adele’s album. The primary data was taken from the 36 song lyrics of Adele, written by Adele and other songwriters as data source. The data was collected by using documentation method by applying note taking technique. Thus, the data were also checked with source which provides the information and list of English idioms. In the analysis, the classifications of idioms were presented first. The main theories used in the analysis of the data consist of the classifications of idioms proposed by Kvetko (1976). The analysis of meaning comes afterward in order to categorized the types of meaning of idioms occurred in data source. The theory of meaning comes from Leech (1974). The study found that the 75 idiomatic expressions are found in the songs. The meaning of idiomatic expression had a strong relation with the meaning of the song. Discover the types of idiomatic expressions. They are phrasal idiom and sentence idiom. Obtain also meaning each idiomatic expression of songs. Each song has different meaning.